Design thinking : research, innovation, and implementation - Sanzo, Karen; Scribner, Jay Paredes, 1963-; Wheeler, Jason A.; Maxlow, Kate Wolfe (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Design thinking is a human-centered problem-solving process that organizations can use to address wicked and complex problems of practice. Within the PK-12 space, design thinking has been employed to engage educators in an innovative approach to address challenges like curriculum redesign, instructional engagement, and designing physical spaces. The use of design thinking in the PK-12 space is a result of the evolution of an organizational improvement process that puts people at the center of problem-solving initiatives. Design thinking is seen as both a process and a mindset that enables people to look at problems in new ways and address these problems through creative approaches. In this book we share case studies of PK-12 schools and other educational organizations that have used design thinking, as well as research studies that have studied aspects of design thinking in the PK-12 space. We have brought together a variety of research-based and illustrative case studies around design thinking in PK-12 education that explore the development and implementation of design thinking in practice"-- Provided by publisher.
Keywords: Educational change -- Case studies.; Curriculum planning -- Case studies.; Classroom environment -- Case studies.; Teacher effectiveness -- Case studies.; elektronické knihy; Case studies.; Education -- Teaching -- General.; Teaching staff.; Teaching skills and techniques.; electronic books